Radiophobic Fear-Mongering, Misappropriation of Medical References and Dismissing Relevant Data Forms the False Stance for Advocating Against the Use of Routine and Repeat Radiography in Chiropractic and Manual Therapy - Paul A. Oakley; Deed E. Harrison (SAGE Publishing, 2021)
There is a faction within the chiropractic profession passionately advocating against the routine use of X-rays in the diagnosis, treatment and management of patients with spinal disorders (aka subluxation). These activists reiterate common false statements such as "there is no evidence" for biomechanical spine assessment by X-ray, "there are no guidelines" supporting routine imaging, and also promulgate the reiterating narrative that "X-rays are dangerous." These arguments come in the form of recycled allopathic "red flag only" medical guidelines for spine care, opinion pieces and consensus statements. Herein, we review these common arguments and present compelling data refuting such claims. It quickly becomes evident that these statements are false. They are based on cherry-picked medical references and, most importantly, expansive evidence against this narrative continues to be ignored. Factually, there is considerable evidential support for routine use of radiological imaging in chiropractic and manual therapies for 3 main purposes: 1. To assess spinopelvic biomechanical parameters; 2. To screen for relative and absolute contraindications; 3. To reassess a patient's progress from some forms of spine altering treatments. Finally, and most importantly, we summarize why the long-held notion of carcinogenicity from X-rays is not a valid argument.